Effect of a condensed NBA season on injury risk: An analysis of the 2020 season and player safety - Morikawa, L. H.; Tummala, S. V.; Brinkman, J. C.; Buckner Petty, S. A.; Chhabra, A. (Orthopaedic Journal of Sports Medicine, 2022)
Background: Health and safety concerns surrounding the coronavirus 2019 (COVID-19) pandemic led the National Basketball Association (NBA) to condense and accelerate the 2020 season. Although prior literature has suggested that inadequate rest may lead to an increased injury risk, the unique circumstances surrounding this season offer a unique opportunity to evaluate player safety in the setting of reduced interval rest. Hypothesis: We hypothesized that the condensed 2020 NBA season resulted in an increased overall injury risk as compared with the 2015 to 2018 seasons. Study Design: Descriptive epidemiology study. Methods: A publicly available database, Pro Sports Transactions, was queried for injuries that forced players to miss =1 game between the 2015 and 2020 seasons. Data from the 2019 season were omitted given the abrupt suspension of the league year. All injury incidences were calculated per 1000 game-exposures (GEs). The primary outcome was the overall injury proportion ratio (IPR) between the 2020 season and previous seasons. Secondary measures included injury incidences stratified by type, severity, age, position, and minutes per game. Results: A total of 4346 injuries occurred over a 5-season span among 2572 unique player-seasons. The overall incidence of injury during the 2020 season was 48.20 per 1000 GEs but decreased to 39.97 per 1000 GEs when excluding COVID-19. Despite this exclusion, the overall injury rate in 2020 remained significantly greater (IPR, 1.42 [95% CI, 1.32-1.52]) than that of the 2015 to 2018 seasons (28.20 per 1000 GEs). On closer evaluation, the most notable increases seen in the 2020 season occurred within minor injuries requiring only a 1-game absence (IPR, 1.53 [95% CI, 1.37-1.70]) and in players who were aged 25 to 29 years (IPR, 1.57 [95% CI, 1.40-2.63]), averaging =30.0 minutes per game (IPR, 1.67 [95% CI, 1.47-1.90]), and playing the point guard position (IPR, 1.67 [95% 1.44-1.95]). Conclusion: Players in the condensed 2020 NBA season had a significantly higher incidence of injuries when compared with the prior 4 seasons, even when excluding COVID-19-related absences. This rise is consistent with the other congested NBA seasons of 1998 and 2011. These findings suggest that condensing the NBA schedule is associated with an increased risk to player health and safety.